Predictors of Coordinated and Comprehensive Care Within a Medical Home for Children With Special Healthcare (CHSCN) Needs - Walker, Ashley; Peden, John G.; Emter, Morgan; Colquitt, Gavin (Frontiers in Public Health, 2018)
The purpose of this study was to examine predictors of coordinated and comprehensive care within a medical home among children with special health care needs (CSHCN). The latest version of the National Survey of Children with Special Health Care Needs (NS-CSHCN) employed a national random-digit-dial sample whereby US households were screened, resulting in 40,242 eligible respondents. Logistic regression analyses were performed modeling the probability of coordinated, comprehensive care in a medical home based on shared decision-making and other factors. A total of 29,845 cases were selected for inclusion in the model. Of these, 17,390 cases (58.3%) met the criteria for coordinated, comprehensive care in a medical home. Access to community-based service systems had the greatest positive impact on coordinated, comprehensive care in a medical home. Adequate insurance coverage and being White/Caucasian were also positively associated with the dependent variable. Shared decision-making was reported by 72% of respondents and had a negative, but relatively negligible impact on coordinated, comprehensive care in a medical home. Increasing age, non-traditional family structures, urban residence, and public insurance were more influential, and negatively impacted the dependent variable. Providers and their respective organizations should seek to expand and improve health and support services at the community level.